Globalization and consumer behavior: global marketing strategies implication - homogeneity and heterogeneity (Preliminary Study) - Nezakati, Hossein; Akhoundi, Maryam (International Foundation for Research & Development, 2013)
This research aims to explore consumer behavior and their responses to possible effects of globalization, resulting in adopting different global marketing strategies in an Asian country particularly Malaysia which is so different of European ones, especially, in terms of cultural aspects. Homogeneity and heterogeneity in consumer behavior are the main approaches of this research. Rather than causes hindering the possible phenomena of two-polarity of world economy or empires, to find out companies global marketing strategies are the research objectives. So, this research examines data collected through, respectively, qualitative and quantitative methods and addresses companies’ marketers and consumers. However, due to innumerous affecting variables and multidimensional nature of globalization, at this point of study there is no absolute evidence to show results but the theoretical assumptions on companies’ tendency toward standardization or customization strategies.